(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Indian economy has been based on agriculture for a long time but as returns from traditional agriculture wane, it is necessary to foray into associated activities like fruit and vegetable growing, flower growing etc. to augment farm incomes. The North East region of the country has lagged in the process of economic development as compared to other parts. Horticulture has the potential to energize the process of economic development in the region and ensure economic development of the seven states of NE India. The article attempts to analyze the importance of horticulture for the development of the region while emphasizing the role of an important scheme Horticulture Mission for North East Himalayan States for the purpose.